Kata Bersufiks pada Tajuk Rencana Suara Merdeka dan Implikasinya Terhadap Pembelajaran - Evitasari, Evitasari; , Drs. Yakub Nasucha, M.Hum (2016)
The objectives in this study was to determine (1) use of words suffixed, (2) the meaning of the word suffixed on the editorial newspaper Suara Merdeka, and (3) the implications word suffixed on the editorial newspaper Suara Merdeka to learning Indonesian in SMA Muhammadiyah 2 Gemolong. The research is a qualitative study using descriptive methods. The data source of this research that the editorial in the newspaper Suara Merdeka. The data is in the form of word suffixed. The data collection technique using the technique see and record. Based on the research that 10 editorial in the newspaper Suara Merdeka there were 57 word suffixed. The use of word suffixed {-an} totaled 24 data, word suffixed {-kan} totaled 20 data, word suffixed {-i} totaled 7 data, word suffixed {-nya} totaled 4 data, word suffixed {-is} totaled 1 data. Meaning of word suffixed includes object work/ are in, circumstances related/ size, each, those skilled, affirming relationships, and stated flow/ understand. Morphological study of materials related suffixes can be used as teaching materials in SMA Muhammadiyah 2 Gemolong. Keyword: word suffixed, editorials, learning